Mel fell - Tabor, Corey R. (New York : Balzer + Bray, 2021)
Follow Mel on her journey from downward fall to triumphant flight in this tale of self-confidence and taking a leap of faith.
Kirkus Starred, December 2020
1.4
K-3
Keywords: Kingfishers -- Juvenile fiction; Birds -- Juvenile fiction; Flight -- Juvenile fiction; Self-confidence -- Juvenile fiction; Kingfishers -- Fiction; Birds -- Fiction; Flight -- Fiction; Self-confidence -- Fiction; Animal fiction